THE RELATIONSHIP BETWEEN TRUNK MUSCLES ENDURANCE AND NORMAL BMI AMONG UNIVERSITY STUDENTS WITH SEDENTARY LIFESTYLE (International Journal of Physiotherapy, 2017)
Background: The most important trunk stabilizers are the trunk flexors and extensors. The isometric endurance of the trunk muscles is an essential element for mechanical support of the spine in all positions. The study objectives were to find out the trunk flexors and extensors endurance, its relationship with normal BMI and to find out the ratio of trunk flexors to extensors endurance.Methods: In this correlation study, 50 subjects were selected by convenience sampling method on the basis of inclusion and exclusion criteria from Asia metropolitan university, Malaysia. The trunk flexors and extensors endurance were assessed by Kraus- Weber and Sorenson test respectively. Paired 't' test and Spearman correlation test were used for data analysis.Results: There was a significant difference (p< 0.05) between trunk flexors (65.4± 26.5) and extensors (107.8±41.7) endurance. Trunk extensors endurance was higher than trunk flexors endurance. A two-tailed test of significance indicated that BMI was unrelated to the subject’s TFE, rs (50) = -0.160, p > 0.01 and TEE, rs (50) = -0.162, p >0.01 but there was a significant strong positive relationship between TFE and TEE, rs (50) = 0.68, p < 0.01. The ratio of trunk flexors to extensors was 0.61.Conclusion: The trunk extensors endurance is higher than trunk flexors endurance and BMI has no relationship with trunk flexors and extensors muscle endurance. The ratio of trunk flexors to extensors endurance value is low.